Handbook of Oral Anticoagulation - Lip, Gregory Y H.; Shantsila, Eduard; SpringerLink (Online service) (Tarporley : Springer Healthcare Ltd. : Imprint: Springer Healthcare, 2010)
An overview of the new oral warfarin alternatives, an important new area in therapy for cardiovascular disease, provided by a leading expert. Presented in a concise format Authored by a well-known expert Provides a user-friendly overview of the most important clinical trials
The coagulation pathway and approaches to anticoagulation -- Common clinical indications for anticoagulation -- The vitamin K antagonists and their limitations -- Haemorrhage risks, patient perspectives, and quality-of-life issues -- New oral anticoagulants -- Future directions.
Keywords: Medicine; Cardiology; Medicine & Public Health; Cardiology